Narrowing the skill and knowledge gaps of young researchers on integrated pest and disease management on food legumes in Ethiopia - Kemal, Seid Ahmed; Kumari, Safaa (2023)
Many of young researchers working in plant protection lack skills and knowledge on pest and disease identification, disease/pest measurements, pest, and disease dynamics, IPDM options, and different aspects of conducting plant protection research and generating quality data. Skill and knowledge gaps are pronounced mainly on emerging and new diseases affecting food legumes. An additional objective of the training was to train the researchers in evaluating breeding lines together with breeders. Three days of training October 11-13, 2022) were organized for young researchers from Federal and Regional research centers at the Ethiopian Institute of Agricultural Research and a half-day field visit.